Cross-Cultural Stylistic Variations In English And Uzbek News Headlines - Rakhimova Gavkharoy Muyidin kizi (Zien Journals, 2025)
This paper investigates cross-cultural stylistic differences between English and Uzbek news headlines. By examining a range of print and digital headlines, the study identifies key differences in syntactic structures, lexical choices, and pragmatic features. The findings reveal how cultural norms, media traditions, and linguistic systems shape headline construction in each language. These insights have implications for translation, journalism, and intercultural communication.
Keywords: stylistics; cross-cultural communication; English